On the latency and jitter evaluation of software defined networks - Paulson Eberechukwu Numan; Kamaludin Mohamad Yusof; Muhammad Nadzir Bin Marsono; Sharifah Kamilah Syed Yusof; Mohd Husaini Bin Mohd Fauzi; Salawu Nathaniel; Elizabeth N. Onwuka; Muhammad Ariff Bin Baharudin (Institute of Advanced Engineering and Science, 2019)
Conventional networking devices require that each is programmed with different rules to perform specific collective tasks. Next generation networks are required to be elastic, scalable and secured to connect millions of heterogeneous devices. Software defined networking (SDN) is an emerging network architecture that separates control from forwarding devices. This decoupling allows centralized network control to be done network-wide. This paper analyzes the latency and jitter of SDN against a conventional network. Through simulation, it is shown that SDN has an average three times lower jitter and latency per packet that translate to improved throughput under varying traffic conditions.